Spatiotemporal distribution characteristics and environmental control factors of biogenic dimethylated sulfur compounds in the East China Sea during spring and autumn. (23rd October 2017) - Jian, Shan; Zhang, Hong‐Hai; Zhang, Jing; Yang, Gui‐Peng
Abstract: Biogenic dimethylated sulfur compounds could take part in the metabolic process of algal cells and are the key compounds in the biological cycle of sulfur in the marine system. In this study, seasonal and spatial variations of biogenic dimethylated sulfur compounds, including dimethylsulfide (DMS), dimethylsulfoniopropionate (DMSP), and dimethylsulfoxide (DMSO), and oceanographic parameters influencing their concentrations were measured in the East China Sea (ECS) during two cruises from 22 October 2015 to 13 November 2015 and from 31 May 2016 to 14 June 2016. Significant spatial variability was observed in seawater dimethylated sulfur compound concentrations with higher concentration in spring. In most cases, concentrations of DMS, particulate DMSP, and particulate DMSO showed significant relationships with the concentration of chlorophyll a under highly variable hydrographic conditions. In spring, bacterial abundance also significantly influenced DMS distribution. Photodegradation experiments showed that enhanced UV radiation could increase DMS photodegradation rate, and low seawater pH could facilitate DMS degradation rate under UVB radiation while it was decreased under UVA radiation. Preliminary estimates for the sea‐to‐air fluxes of DMS in spring showed a 2.3 μmol m −2 d −1 increase over autumn flux. Compared with total DMS emission of the global ocean to atmosphere, the contribution of the ECS to global DMS emissions was not negligible. At Sta. DH6‐1, the contribution of biological consumption to DMS removal (85%) was higher than those of photolysis (10%) and sea‐to‐air exchanges (4%). These findings reveal that biological consumption probably dominates removal of DMS at this station.